Impact of Self-Contained Breathing Apparatus on Air Gaps in Structural Firefighting Personal Protective Clothing - Josephine Bolaji; Meredith McQuerry (Applied Sciences)
The self-contained breathing apparatus (SCBA) is an integral part of the structural firefighting personal protective equipment (PPE) ensemble. However, when donned, it adds significant weight and restriction, interfering with the fit of the turnout suit and the ventilation within the clothing system. This may result in a reduction of air gaps within the clothing microclimate, quickening the onset of heat strain. Therefore, the purpose of this study was to assess the impact of the SCBA on air gaps in structural firefighting turnout suits. Nine active-duty male firefighter participants were scanned in a three-dimensional body scanner in four garment configurations (compression, base layers, turnout suit, and turnout with SCBA). Torso volume, surface area, and air gaps were calculated alongside ease measurements. Findings demonstrated a 59% increase in torso volume when donning the turnout suit over base layers compared to a 1.2% reduction in torso volume when donning the SCBA. The change in torso air gap volume and distance were also found to be negligible when donning the SCBA. This study lays the foundation for full systems ensemble research needed to better understand how the design, weight, and fit of the SCBA impacts the thermal comfort, mobility, and protection of structural firefighters.